Degradation of dyes by fungi: An overview on recent updates - Nagraj; Pankaj Kumar Chaurasia; Shashi Lata Bharati; Nagendra Sharma; Jaynath Kumar; Azhagu Madhavan Sivalingam (The Microbe)
Dyes are colored organic compounds widely used in the field of painting, medicine, textiles, paper and plastic factories and many other industrial sectors. Tendency of dye molecules to firmly fix with fabric make them essentially important in textile sectors. Besides these useful roles of dyes, they are also considered as harmful organic pollutants. Unused dyes and their different byproducts released from industrial sectors are the serious concern for human health as well as aquatic lives. Different methods for the detoxification of dyes molecules have been studied like physical, chemical, and biological methods. Biological methods utilize the microbial sources (primarily fungi, bacteria, yeast, and microbial enzymes) and plants for the degradation and remediation of dyes pollutants. Biological methods are relatively inexpensive and ecofriendly in comparison with conventional physical and chemical methods due to their strong biosorption and dye mineralizing efficiency. Fungal assisted dyes removal involves the mechanism of biosorption, bioaccumulation, and biodegradation processes. Fungal lignolytic enzymes (Laccase, Manganese peroxidase, and Lignin peroxidase) have potential role in the effective degradation of various dye molecules, especially azo-dyes by attacking on their more vulnerable bonds. Such enzymes break the weaker bonds and convert the broken moieties in to lesser toxic or no-toxic forms. Although, fungal bioremediation of dyes molecules is an effective method of biodegradation due to their different enzyme secretion, however, there are many challenges in their industrial scale application like longer period requirement in the fungal treatment method, alkaline nature of textile effluents, and management of different factors like temperatures, pHs, concentration of dye molecules, time of stirring or agitation and many others in dye polluted water system. Thus, this review assesses the fungal role in depollution of dyes, its mechanism, factors affecting the rate of degradation, and effectiveness of various studies in field. Along with discussions on the fungal efficiency in dye removal; major challenges in the application of fungal technology for dyes degradation at industrial scale have also been be described and evaluated.